Potassium Competitive Acid Blockers: A New Paradigm For The Management of Stomach Acid Disorders - Gerie Amarendra; Wawan Kurniawan; Mizanul Adli (Fakultas Kedokteran Universitas Sriwijaya, 2023)
Proton pump inhibitors (PPIs) are the main therapy for stomach acid disorders to date. The disadvantage of PPI is the difficulty of controlling symptoms at night, such as tightness, chest pain, and coughing cough. Potassium competitive acid blockers (P-CAB) are a new class in the management of stomach acid disorders. Potassium competitive acid blockers work by a different mechanism, which binds non-covalently to H+/K+-ATPase. This mechanism results in a faster, stronger, and long-lasting suppression effect of gastric acid production. Besides being able to cure gastric complaints at night, P-CAB increases the success of Helicobacter pylori eradication. The safety of the use of this P_CAB drug, according to research is quite mild and acceptable. Currently, examples of P-CAB groups on the market are vonoprazan and tegoprazan. This narrative review is intended to provide further insight into this potassium competitive acid blocker (P-CAB) class of drugs.